Uncovering neurodevelopmental windows of susceptibility to manganese exposure using dentine microspatial analyses - Henn, Birgit Claus (Environ Res, 2018)
BACKGROUND: Associations between manganese (Mn) and neurodevelopment may depend on dose and exposure timing, but most studies cannot measure exposure variability over time well. OBJECTIVE: We apply temporally informative tooth-matrix biomarkers to uncover windows of susceptibility in early life when Mn is associated with visual motor ability in childhood. We also explore effect modification by lead (Pb) and child sex. METHODS: Participants were drawn from the ELEMENT (Early Life Exposures in MExico and NeuroToxicology) longitudinal birth cohort studies. We reconstructed dose and timing of prenatal and early postnatal Mn and Pb exposures for 138 children by analyzing deciduous teeth using laser ablation-inductively coupled plasma-mass spectrometry. Neurodevelopment was assessed between 6–16 years of age using the Wide Range Assessment of Visual Motor Abilities (WRAVMA). Mn associations with total WRAVMA scores and subscales were estimated with multivariable generalized additive mixed models. We examined Mn interactions with Pb and child sex in stratified models. RESULTS: Levels of dentine Mn were highest in the second trimester and declined steeply over the prenatal period, with a slower rate of decline after birth. Mn was positively associated with visual spatial and total WRAVMA scores in the second trimester, among children with lower (<median) tooth Pb levels: one standard deviation (SD) increase in ln-transformed dentine Mn at 150 days before birth was associated with a 0.15 [95% CI: 0.04, 0.26] SD increase in total score. This positive association was not observed at high Pb levels. In contrast to the prenatal period, significant negative associations were found in the postnatal period from ~6 to 12 months of age, among boys only: one SD increase in ln-transformed dentine Mn was associated with a 0.11 [95% CI: −0.001, −0.22] to 0.16 [95% CI: −0.04, −0.28] SD decrease in visual spatial score. CONCLUSIONS: Using tooth-matrix biomarkers with fine scale temporal profiles of exposure, we found discrete developmental windows in which Mn was associated with visual-spatial abilities. Our results suggest that Mn associations are driven in large part by exposure timing, with beneficial effects found for prenatal levels and toxic effects found for postnatal levels.